Posyandu cadre training on stress management with five finger hypnosis for the elderly with hypertension problems - Ellia Ariesti; Mohammad Ali Sodikin; Febrina Secsaria Handini (Universitas Muhammadiyah Magelang, 2022)
Tambakasri Village is located in Tajinan District, Malang Regency which has posyandu for the elderly and toddlers. Currently, the posyandu cadres have received training from the Tajinan Health Center, which focuses on the prevention and treatment of physical problems. However, one of the consequences of the pandemic is that many elderly which have hypertension health problems suffer stress, so training in a non-pharmacological way is required. As a result, the goal of this program is to improve the ability of health cadres in Tambakasri Village to use the five-finger hypnosis technique to improve the health of the elderly, particularly those with hypertension. This activity was judged successful based on four indicators, they are achieving the target number of training participants, the training objectives, the planned material targets, and participants' mastery of the material. The benefits obtained by health cadres include the ability to guide and assist the general public, particularly the elderly with hypertension who are stressed.